The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1101/gad.267393.115
|View full text |Cite
|
Sign up to set email alerts
|

Foxa2 and Cdx2 cooperate with Nkx2-1 to inhibit lung adenocarcinoma metastasis

Abstract: Despite the fact that the majority of lung cancer deaths are due to metastasis, the molecular mechanisms driving metastatic progression are poorly understood. Here, we present evidence that loss of Foxa2 and Cdx2 synergizes with loss of Nkx2-1 to fully activate the metastatic program. These three lineage-specific transcription factors are consistently down-regulated in metastatic cells compared with nonmetastatic cells. Knockdown of these three factors acts synergistically and is sufficient to promote the meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
65
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(71 citation statements)
references
References 33 publications
6
65
0
Order By: Relevance
“…Independent Component Analysis (ICA), targeted pair-wise differential expression analysis, and gene set enrichment analysis (GSEA) were performed as described in (45). All primary RNA-seq data are available at Gene Expression Omnibus (GSE71877).…”
Section: Methodsmentioning
confidence: 99%
“…Independent Component Analysis (ICA), targeted pair-wise differential expression analysis, and gene set enrichment analysis (GSEA) were performed as described in (45). All primary RNA-seq data are available at Gene Expression Omnibus (GSE71877).…”
Section: Methodsmentioning
confidence: 99%
“…In human breast cancer cells, the activation of key stem cells pathways, such as Wnt and Notch signaling, is also important for supporting their colonization in xenograft mouse models (Oskarsson et al, 2011). And mouse models of lung adenocarcinoma have revealed that metastatic progression is associated with a dedifferentiation program, mediated by loss of Nkx2-1 expression, which resembles programs operating in stem-like states (Li et al, 2015; Winslow et al, 2011). Thus, it appears that the metastatic potential of a carcinoma is closely related to its ability to dispatch populations of CSCs that can re-initiate tumor growth following arrival at distant sites (Oskarsson et al, 2014).…”
Section: Metastatic Colonizationmentioning
confidence: 99%
“…1) based on sequence similarity within and outside of the forkhead box (Hannenhalli and Kaestner, 2009;Kaestner et al, 1999). In many cases, the homozygous deletion of just one Fox gene leads to embryonic or perinatal lethality and, in humans, mutations in or the abnormal regulation of Fox genes are associated with developmental disorders and diseases such as cancer Li et al, 2015a;Wang et al, 2014b;Zhu et al, 2015;DeGraff et al, 2014;Halmos et al, 2004;Ren et al, 2015;Jones et al, 2015;Habashy et al, 2008), Parkinson's disease (Kittappa et al, 2007), autism spectrum disorder (Bowers and Konopka, 2012), ocular abnormalities (Acharya et al, 2011), defects in immune regulation and function (Mercer and Unutmaz, 2009) and deficiencies in language acquisition (Takahashi et al, 2009); see Table 1 for a comprehensive overview of Fox transcription factor expression patterns and their association with developmental disorders and disease.…”
Section: An Overview Of Fox Transcription Factorsmentioning
confidence: 99%